2013
DOI: 10.1007/s11626-013-9588-2
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin-induced proliferation involves MEK partner 1 (MP1)

Abstract: The peptide hormone gastrin is an important factor for the maintenance and homeostasis of the gastric mucosa. We show that gastrin stimulates proliferation in a dose-dependent manner in the human gastric adenocarcinoma cell line AGS-GR. Furthermore, we demonstrate that the MAPK scaffold protein MEK partner 1 (MP1) is important for gastrin-induced phosphorylation of ERK1 and ERK2 and that MP1 promotes gastrin-induced proliferation of AGS-GR cells. Our results suggest a role of MP1 in gastrin-induced cellular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…We have recently shown that the gastrin induced MAPK scaffold protein MEK partner 1 (MP1) is important for gastrin induced phosphorylation of ERK1 and ERK2 in the human gastric adenocarcinoma cell line AGS-G R [53]. Qualitative and quantitative differences in ERK activity can also be regulated at the receptor level [49].…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that the gastrin induced MAPK scaffold protein MEK partner 1 (MP1) is important for gastrin induced phosphorylation of ERK1 and ERK2 in the human gastric adenocarcinoma cell line AGS-G R [53]. Qualitative and quantitative differences in ERK activity can also be regulated at the receptor level [49].…”
Section: Resultsmentioning
confidence: 99%
“…Gastrin and/or its receptor have been identified in a number of tissues and tumor types (e.g., Barrett's esophagus, gastric adenocarcinoma, pancreatic adenocarcinoma, and colonic adenocarcinoma) in which it may promote growth and induce oncogenic transformation [31]. Amidated gasrin-34 and gasrin-17, as well as the CCK2R, are detectable in 80% of human gastric adenocarcinomas [32 & ].…”
Section: Key Pointsmentioning
confidence: 99%
“…We and others have shown that gastrin regulates several important cellular processes in the gastric epithelium and in adenocarcinoma cells including proliferation [1], anti-apoptosis [2], [3], [4], migration [5] and invasion [6]. Functional genomics approaches have identified a range of new gastrin target genes [3], [4], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%